Conceptual and methodological issues in the study of the personality-and-culture relationship - Allik, Jüri; Realo, Anu; McCrae, Robert R. (Frontiers in Psychology, 2023)
Culture-and-personality studies were central to social science in the early 20th century and have recently been revived (as personality-and-culture studies) by trait- and cross-cultural psychologists. In this article we comment on conceptual issues including the nature of traits and the nature of the personality/culture relationship and describe methodological challenges in understanding associations between features of culture and aspects of personality. We give an overview of research hypothesizing the shaping of personality traits by culture, reviewing studies of indigenous traits, acculturation and sojourner effects, birth cohorts, social role changes, and ideological interventions. We also consider the possibility that aggregate traits affect culture, through psychological means and gene flow. In all these cases we highlight alternative explanations and the need for designs and analyses that strengthen the interpretation of observations. It is clear that culture has dramatic effects on the thoughts, feelings, and behaviors from which we infer traits, but it is not yet clear whether, how, and in what degree culture shapes traits themselves.